Hubungan tingkat kecukupan zat gizi, lean body mass, dan aktivitas fisik dengan kepadatan tulang pada mahasiswa Universitas Udayana Denpasar - Dewi, Ni Putu Puspita Adhytiarini; Susanto, Hardhono; Rosidi, Ali (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2016)
Background: Bone formation and peak bone mass determine with bone density in adulthood related with osteopenia or osteoporosis. It could be influenced by nutrition intakes, lean body mass, and physical activity.Objective: to analyze the correlation between nutritional adequacy, lean body mass, physical activity and bone mineral density in Udayana University Economicâ€™s students, Denpasar. Methods: Cross-sectional study design was done to female students of Faculty of Economic and Business, Udayana University, Denpasar. Seventy five subjects were choosen by simple random sampling. Results: Research subjects were aged 20-25 years old. The mean t-score of bone mineral density is -0,363 Â± 1,057. Research subjects were classified as low bone density (osteopenia) 26,7% and 73,3% are normal. Intakes of animal protein (p = 0,042) and lean body mass (p = 0,011) are related with bone mineral density protein (p = 0,955) but not on intakes of vitamin A (p = 0,249), vitamin C (p = 0,632), vitamin D (p = 0,864), calcium (p = 0,724), iron (p = 0,768), magnesium (p = 0,689), phosphorus (p = 0,716), and physical activity (p = 0,254). There were a positive trend on the level of protein, vitamin A, vitamin C, vitamin D, calcium, iron, magnesium and phosphorus sufficiency.Conclusions: Intakes of Animal protein, lean body mass and physical activity related with bone mineral density but not on protein, vitamin A, vitamin C, vitamin D, calcium, iron, magnesium, and phosphorus intake.